A case report on psychogenic non-epileptic disorder - Jagadheeshwari, M; Keshavini, S; Dhivya, K (Indian Journal of Case Reports, 2024)
Psychogenic non-epileptic seizure (PNES) involves attacks that act as epilepsy-related seizures. PNES is more likely to affect women than men and utmost generally begins in the youth. Epileptic seizures generally last between 30 and 120 s depending on the type, while PNES occurrences generally last for two to five twinkles. Features that are common in PNES but rarer in epilepsy include smelling the tip of the lingo, seizures lasting further than two twinkles (easiest factor to distinguish), seizures having a gradational onset, a shifting course of complaint inflexibility, the eyes being closed during a seizure, and side to side head movements. Psychotherapy is the most constantly used treatment, which might include cognitive behavioral remedy or remedy to retrain the physical symptoms and allow the existent to recapture control of the attacks. There is also some substantiation supporting picky serotonin reuptake asset antidepressants. Here, we present the case of a 45-year-old female presented with the chief complaints of giddiness in the right ear for 1 week, vomiting for 2 days, and two episodes of bilateral upper and lower body jerks. Later on, she was diagnosed with PNES.